2021
DOI: 10.18295/squmj.4.2021.004
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Perception Towards Spectacle Wear among Student Population of University of Buraimi, Oman

Abstract: Objectives: The study aims to evaluate the barriers and perception towards spectacle wear among student population of University of Buraimi, Oman. Methods: This descriptive, questionnaire based, cross-sectional study was conducted between December 2017 and May 2018.  To evaluate participant’s barriers and perception towards spectacle wear, a self-designed, validated questionnaire prepared in English language, obtained responses from 170 a university student population within the Sultanate of Oman. Chi-square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…These results differed from the findings in a study conducted in Oman, which showed that some of the barriers to wearing spectacles were losing or breaking the spectacles. 24 A different study, in Nigeria, awareness among spectacle wearers was relatively high. However, most participants reported their fear of complications.…”
mentioning
confidence: 96%
“…These results differed from the findings in a study conducted in Oman, which showed that some of the barriers to wearing spectacles were losing or breaking the spectacles. 24 A different study, in Nigeria, awareness among spectacle wearers was relatively high. However, most participants reported their fear of complications.…”
mentioning
confidence: 96%